Relationship Between Sitting Position and Sitting Duration with Low Back Pain Complaints in Back Office - Sarbiah, Andi; Maulina, Diina; Sunsaru, Agung; Wijaya, Juhanda Kartika (Journal La Medihealtico, 2024)
Low Back Pain is a musculoskeletal disorder resulting from incorrect implementation of ergonomics. The main symptoms of Low Back Pain is pain in the spinal area of the back. This study aims to determine the relationship between sitting position and sitting time with Low Back complaints Pain in back office at the Mandiri Inhealth Batam Operational Office in 2020. The research method used is a quantitative method with an analytical survey research design with a cross research design sectional on each subject using the Chi- square test , namely comparing the frequency of occurrence (observation) with the frequency of expectations (expectations) with a sample of 30 respondents. From the results of this research, it was concluded that there was a relationship between sitting position (P- Value = 0.003) and sitting time (P- Value = 0.030) with Low Back complaints. Pain . Advice for workers to pay attention to their sitting position and take the time to stretch their muscles when doing work to prevent or reduce complaints of Low Back Pain and for companies providing health education about ergonomics.